2017
DOI: 10.1002/2016ef000472
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing phosphorus limitations in natural terrestrial ecosystems in carbon cycle models

Abstract: Most of the Earth System Models (ESMs) project increases in net primary productivity (NPP) and terrestrial carbon (C) storage during the 21st century. Despite empirical evidence that limited availability of phosphorus (P) may limit the response of NPP to increasing atmospheric CO2, none of the ESMs used in the previous Intergovernmental Panel on Climate Change assessment accounted for P limitation. We diagnosed from ESM simulations the amount of P need to support increases in carbon uptake by natural ecosystem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 71 publications
1
70
0
1
Order By: Relevance
“…The availability of key nutrients, such as K and P, are predicted to decrease the sensitivity of ecosystems to increasing CO 2 emissions and warming (Fernández‐Martínez et al, ; Penuelas, Ciais, et al, ; Wang, Zhang, et al, ). For example, climate‐system models have predicted that limited P availability and corresponding imbalances in N:P ratios will decrease the capacity of terrestrial ecosystems to remove CO 2 (Goll et al, ; Penuelas et al, , 2017; Sun et al, ; Wang, Zhang, et al, ). Similarly, other studies report that recent climatic warming has increasingly decreased the capacity of the biosphere to store C (Fernández‐Martínez et al, ), and only forests with nutrient‐rich soil had higher net primary production (NPP) in response to increases in gross primary productivity (Fernández‐Martínez et al, ).…”
Section: Impacts Of Shifts In the N:p Ratios Of Human Inputs On Organmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of key nutrients, such as K and P, are predicted to decrease the sensitivity of ecosystems to increasing CO 2 emissions and warming (Fernández‐Martínez et al, ; Penuelas, Ciais, et al, ; Wang, Zhang, et al, ). For example, climate‐system models have predicted that limited P availability and corresponding imbalances in N:P ratios will decrease the capacity of terrestrial ecosystems to remove CO 2 (Goll et al, ; Penuelas et al, , 2017; Sun et al, ; Wang, Zhang, et al, ). Similarly, other studies report that recent climatic warming has increasingly decreased the capacity of the biosphere to store C (Fernández‐Martínez et al, ), and only forests with nutrient‐rich soil had higher net primary production (NPP) in response to increases in gross primary productivity (Fernández‐Martínez et al, ).…”
Section: Impacts Of Shifts In the N:p Ratios Of Human Inputs On Organmentioning
confidence: 99%
“…N and P concentrations and ratios at regional scales generally tend to differ between agricultural areas with no or low levels of livestock and areas with higher densities of livestock. The ratios of N:P inputs tend to be higher in areas with low livestock densities that are treated with inorganic fertilizer (Dupas et al, 2015;Romero et al, 2019;Sardans et al, 2012b;Sun et al, 2017).…”
Section: Spatial Heterogeneity In Anthropogenic N and P Imbalancesmentioning
confidence: 99%
“…In our analysis, the clay variable includes not only clay minerals but also secondary minerals such Fe and Al oxyhydroxides, as it follows the particle size classification. Fe and Al oxyhydroxides are known to be key in inorganic P exchange behavior (Achat et al, 2016;Syers et al, 2008). For the samples where data on oxalate-and dithionite-extractable Al and Fe were available (n = 41-43), simple regression showed only weak correlations with MRTs and only significance for MRT of NaOH-P with oxalateextractable Al, dithionite-extractable Fe, and the sum of dithionite-extractable Al and Fe as explanatory variables (adjusted R 2 ≤ 0.16, p<0.05; data not shown).…”
Section: Response Variable Multiple-regression Modelmentioning
confidence: 99%
“…In recent years, land surface models (LSMs) have developed from carbon (C)-only models to C-N-coupled models, and there is now a drive to include P cycle processes (Reed et al, 2015). The inclusion of C-N-P biogeochemistry is thought to be essential for understanding the C budget of ecosystems with P-poor soils (Ellsworth et al, 2017), and has been demonstrated to reduce estimates of future global C sequestration (Goll et al, 2012;Sun et al, 2017). P cycle processes can be split broadly into those that control external supply, namely the amount of P that is present in the soil and available to plants, and those that control the plant internal demand, namely the P concentration inside plant tissues required to sustain plant growth and function (Jin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Modelling studies and reviews thus far have focused principally on the question of the magnitude of external supply and on improving representations of soil processes and plant acquisition strategies (Reed et al, 2015). The internal P demand, which ultimately drives plant productivity, has been mainly derived from heuristic relationships that assume growth is constrained by empirical C : N : P ratios (Achat et al, 2016;Sun et al, 2017). This empirical approach does not provide any indication of how plants use the acquired P for metabolism and growth nor how the tissue P concentration affects the physiology.…”
Section: Introductionmentioning
confidence: 99%